Synergistic effect of nanodiamond and titanium oxide nanoparticles on the mechanical, thermal and electrical properties of pitch‐derived carbon foam composites. Issue 12 (27th July 2021) - Khan, Muhammad; Tiehu, Li; Zaidi, Syed Basit Ali; Javed, Elisha; Hussain, Amjad; Hayat, Asif; Zada, Amir; Alei, Dang; Ullah, Azeem
Abstract: Titanium oxide (TO)‐ and functionalized nanodiamond (FND)‐reinforced carbon foam ( CF ) composites were prepared by the direct pyrolysis of TO, FND and a mixture of mesophase coal tar pitch. The effects of TO and FND loadings on the microstructure and functional properties of the CF composites were studied. The obtained microstructures of the CF composites showed that both nanofillers have an influential role in the formation of porous morphology of CF. Moreover, the additive aspects of TO and FND were further studied in terms of mechanical, thermal and electrical properties. The results revealed that compressive strength increased up to 20.21 MPa, thermal conductivity was as high as 32.33 W m −1 K −1 at elevated temperature and electrical conductivity was 23.24 × 10 3 S m −1 . The results show that FND particles are well appropriate to meliorate the fabrication of TO nanoparticles in CF to build up a solid connection between the nanoparticles and CF for the improvement of the mechanical, thermal and electrical properties of CF composites. © 2021 Society of Industrial Chemistry. Abstract : 1. The novel preparation of TO/CF and hybrid TO‐FND/CF composites. 2. Comparison and effect of additive loading on the microstructure and various properties of CF composites. 3. Excellent mechanical, thermal and electrical behavior of TO‐FND/CF composites at 3 wt.% additive loadings.